A comparative study on legal statutes of DNA investigation procedures in Malaysia and Australia / Nur Aliaa Mat Jusoh..[et al.] - Mat Jusoh, Nur Aliaa; Rozali, Nur Amirah; Shuhaimi, Nur Shahirah; Abu Kasim, Rafidah; Rahayud-din, Rozanna (2010)
The incorporation of forensic DNA identification technology into the criminal justice process of a widening number of States has been fast and far-reaching. From the introduction of genetic fingerprinting in high profile cases of serious crime in the mid 1980s, to the now routine use of genetic profiling in volume crime investigation, DNA identification makes an important contribution to the detection of crime and to the construction of prosecution cases for courtroom hearings. Such identifications typically involve the collection of biological material discovered at crime scenes, the profiling of DNA extracted from this material, and the comparison of the profile obtained with existing DNA profiles of offenders held on a forensic database. This project paper is based on an analysis of the legal statutes on forensic DNA investigation which have been used as an authority for the identification of criminal suspects in support of crime investigation. It discusses the enactment of Malaysia's DNA Identification Act 2009, together with the establishment of the DNA Databank as a tool for solving crimes in this country. The DNA Act, which created the DNA Databank which is managed by the Royal Malaysian Police assisted by the Department of Chemistry Malaysia, is the first parliamentary statute that governs forensic DNA investigation. The Personal Data Protection Act 2009 was also enacted to act as a legal safeguard. Since the DNA Act is recently enacted, our project paper provides a comparative analysis on the legal statutes of forensic DNA investigation in Malaysia and the Commonwealth of Australia. The study will emphasize on the legislative framework and protection of human rights in the DNA Identification Act 2009. The Australian statutes on forensic DNA investigation like the Crimes Act 1914, and the Privacy Act 1988 act as good models when dealing with forensic DNA investigation, will also be examined.